2012
DOI: 10.1063/1.4712108
|View full text |Cite
|
Sign up to set email alerts
|

Annealing to mitigate pitting in electropolished niobium coupons and SRF cavities

Abstract: Ongoing studies at Fermilab investigate whether dislocations and other factors instigate pitting during cavity electropolishing (EP), despite careful processing controls and the inherent leveling mechanism of EP itself. Here, cold-worked niobium coupons, which exhibited increased tendencies for pitting in our past study, were annealed in a high vacuum furnace and subsequently processed by EP. Laser confocal scanning microscopy and special defect counting algorithms were used to assess the population of pits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It would although make it less intense [50]. Impurities or inclusions introduced in the EBW region of SRF cavities also present similar problems of pitting for EP of niobium [48]. Sulphide inclusions in nickel have been found to be the site where pits nucleate during anodic dissolution of nickel [49].…”
Section: Other Factors Resulting In Pitting During Electropolishingmentioning
confidence: 99%
See 1 more Smart Citation
“…It would although make it less intense [50]. Impurities or inclusions introduced in the EBW region of SRF cavities also present similar problems of pitting for EP of niobium [48]. Sulphide inclusions in nickel have been found to be the site where pits nucleate during anodic dissolution of nickel [49].…”
Section: Other Factors Resulting In Pitting During Electropolishingmentioning
confidence: 99%
“…The application of current and voltage on the polishing plateau is a necessary condition to obtain a pit free surface but not a sufficient condition. A multitude of reasons have been attributed to be responsible for pitting some of which include (i) oxygen evolution at the surface getting polished, (ii) hydrogen evolved on the cathode, (iii) inclusions on the surface, (iv) stresses on the surface, (v) excess agitation in the polishing bath, and (vi) external treatments given to the surface [3,4,28,[48][49][50][51][52][53][54].…”
Section: Phenomenon Of Pitting In Anodic Dissolution Of Metals and Al...mentioning
confidence: 99%
“…Increased chemical activity due to hydrogen and hydrogen bubbles were plausible causes of pits. A follow-up experiment [12] showed that high-vacuum annealing to recover cold work prior to the EP experiment improved this sensitivity. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Increased chemical activity due to hydrogen and hydrogen bubbles were plausible causes of pits. A follow-up experiment [12] showed that high-vacuum annealing to recover cold work prior to the EP experiment improved this sensitivity. Reference [12] recommended changing the cavity processing sequence to put annealing ahead of chemical polishing as a preventative measure against pitting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation